Demand and Supply Curves in Political Markets : Understanding the Problem of Public Goods and Why Governments Fail Them - Khemani, Stuti (World Bank, Washington, DC, 2017)
This paper brings the economic tools of demand and supply curves to better understand how political markets shape the selection of government policies. It does so to tackle a problem at the intersection of political science and economics: government failure to pursue policies on the basis of sound technical evidence. Too often, the leaders who wield policy-making power within governments deliberately and knowingly ignore sound technical advice, or are unable to pursue it despite the best of intentions, because of political constraints. The paper shows how the prevailing dominant explanation for suboptimal policies and weak institutions, of special interest and elite capture, can be understood as the selection of a point on the political demand curve by oligopolistic political competition. Further, it shows how elite capture is only one of many possible outcomes, and is endogenous to preferences and beliefs in society. Preferences in society for public goods (or the lack thereof), and beliefs about how others are behaving in the public sector, are the primitive or fundamental elements driving the shapes of political demand and supply curves and thence the selection of public policies and institutions. This framework highlights the need for future research to understand where political preferences and beliefs come from, which is essential to the design of institutions that address problems of public goods.